Forbidden fruit sex & religion in the lives of American teenagers - Regnerus, Mark.; Oxford eBooks (Oxford : Oxford University Press, 2007)
'Forbidden Fruit' tells the definitive story of the sexual values and practices of American teenagers, paying particular attention to how participating in organised religion shapes sexual decision-making.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Teenagers -- Religious life -- United States; Teenagers -- Sexual behavior -- United States; Teenagers -- United States -- Conduct of life; Sex -- Religious aspects; Electronic books